Indian social safety net programs as platforms for introducing wheat flour fortification: A case study of Gujarat, India: - Fiedler, John L.; Babu, Sunil; Smitz, Marc-Francois; Lividini, Keith; Bermudez, Odilia I. (SAGE Publications, 2012)
Micronutrient deficiencies exact an enormous health burden on India. The release of the National Family Health Survey results—showing the relatively wealthy state of Gujarat having deficiency levels exceeding national averages—prompted Gujarat officials to introduce fortified wheat flour in their social safety net programs (SSNPs).To provide a case study of the introduction of fortified wheat flour in Gujarat's Public Distribution System (PDS), Integrated Child Development Scheme (ICDS), and Mid-Day Meal (MDM) Programme to assess the coverage, costs, impact, and cost-effectiveness of the initiative.India's 2004/05 National Sample Survey data were used to identify beneficiaries of each of Gujarat's three SSNPs and to estimate usual intake levels of vitamin A, iron, and zinc. Comparing age- and sex-specific usual intakes to Estimated Average Requirements, the proportion of the population with inadequate intakes was estimated. Postfortification intake levels and reductions in inadequate intake were estimated. The incremental cost of fortifying wheat flour and the cost-effectiveness of each program were estimated.When each program was assessed independently, the proportion of the population with inadequate vitamin A intakes was reduced by 34% and 74% among MDM and ICDS beneficiaries, respectively. Both programs effectively eliminated inadequate intakes of both iron and zinc. Among PDS beneficiaries, the proportion with inadequate iron intakes was reduced by 94%.Gujarat's substitution of fortified wheat flour for wheat grain is dramatically increasing the intake of micronutrients among its SSNP beneficiaries. The incremental cost of introducing fortification in each of the programs is low, and, according to World Health Organization criteria, each program is “highly cost-effective.” The introduction of similar reforms throughout India would largely eliminate the inadequate iron intake among persons participating in any of the three SSNPs and would have a significant impact on the global prevalence rate of inadequate iron intake.